Synchronization of RPS English for Broadcasting with Departments at University of Bina Sarana Informatika (Student Perception and Their Effect on Online Learning) - Juniato Sidaruk; Jimmi Jimmi (Universitas Musamus, 2022)
RPS (Rencana Pembelajaran Semester – Semester Learning Plan) is a document contains the framework or outline of learning plan for one semester. The RPS is used by the lecturer and for students. It is as the guideline in learning activities in order to reach the expected outcome. As there is expected outcome, thus it is designed both for lecturer and students and also for the principal, of subject. The RPS can be viewed from students side by having perception test. This perception test will perform either the RPS is synchronous with the students substantial needs by their department. Through perception, students will have notion of something, synchronicity. This research aims at (1) presenting perception of students from Broadcasting Department at Bina Sarana Informatika University on the RPS for English for Broadcasting subject; (2) viewing the influence of RPS through online learning in the Covid-19 pandemic era. This research is conducted by giving a questionnaire to students. Then, it is discussed and analyzed either by qualitative or quantitative research. Students from broadcasting semester IV are taken as an example in this research. There are 35 students was taken questionnaire. The data analysis are using the form of Spearman hypothesis test. The result shows that (1) students perception on RPS synchronousity is Synchronous; (2) There is no influence of students' perceptions of synchronization to their department through online learning. The proof shows that the value of P = 0.124 (P > 0.05) and the value of r xy = 0.294, means the relationship between students' perceptions of synchronicity to their department is not significant or weak.